Фразеология молчания: ‘горло’ и ‘глотка’ в русских фразеологических соматизмах - Kozerenko, Anastasiia; Kreidlin, Grigorii (Wiener Slawistischer Almanach, 2023)
The object of the article are some Russian phraseological units of silence with the words gorlo and glotka (throat): zatknut’ glotku (to shut smb’s mouth), (slova, upreki…) zastryali v glotke/gorle (words stuck in smb’s throat), perekhvatilo gorlo, sdavilo gorlo, kom/komok v gorle (to have a lump in one’s throat). The meanings of the words gorlo and glotka are formulated, the features of the corresponding somatic objects manifested in the phraseological units are described. The main accent of the paper is made on the explications of the meanings of the phraseological units and on their usage. The final part of the article presents a number of statements important for phraseological theory.